Properties of the volume phase in the layerwise growth. Case of origin of new phase above phase boundary at previous layer - Brodskii, R.Ye. (Functional Materials, 2018)
In present work it was studied the formation of transparent windows in a layered-grown sample, each layer of which consists of a basic opaque phase and an additional transparent one, in the case when the islets of an additional phase in a new layer originate above the phase boundary in the previous layer. Also, for this case, the law of changing the fraction σi of the area of the layer occupied by the transparent phase with the layer number i is studied. Distribution densities of windows over the area and their asymptotics in small- and large-scale areas are obtained. The existence of qualitatively different forms of the dependence of σi on the number of the layer as a function of the intensity parameter of formation of islets is shown. This parameter is the value of the average number n of new islets per one islet (the length of the boundary of one islet) in the previous layer.